The Oxford handbook of entrepreneurship and collaboration - edited by Jeffrey J. Reuer, Sharon F. Matusik, and Jessica Jones. (Oxford handbooks online., 2019)
Organisational collaboration has played an important role in the field of strategic management in the last couple of decades. Though the importance of collaboration to entrepreneurship might seem apparent, research on it is distributed across multiple contexts, theoretical perspectives, and units of analysis. The aim of this volume is to highlight this diversity and emphasise the important roles that collaboration plays in value creation, resource acquisition, and the development of entrepreneurial ventures. Interorganisational collaboration involves two or more independent organisations working together under an incomplete contract to accomplish certain objectives. These collaborations might take many forms, ranging from relatively informal or narrow-scope exchanges to equity partnerships.